A novel dual target simultaneous chemiluminescence signal amplification strategy for enhancing sensitivity of multiple biomolecule detection. Issue 48 (28th November 2017) - Li, Jian; Zhao, Jingjin; Li, Shuting; Zhang, Liangliang; Lan, Chuanqing; Huang, Yong; Zhao, Shulin
Abstract : A G-quadruplex DNAzyme and nicking enzyme assisted multiplex chemiluminescence signal amplification based microchip electrophoresis method was developed for simultaneous detection of two trace biomolecules. Abstract : Disease marker detection plays an important role in clinical practice; however, rapid, low-cost and simultaneous detection of multiple trace disease markers remain a challenge because of low abundance of related strategies. Herein, we report a G-quadruplex DNAzyme and nicking enzyme-assisted multiplex chemiluminescence (CL) signal amplification (EMCSA) strategy based on a microchip electrophoresis (MCE) platform for simultaneous detection of two trace target molecules. In this study, two target molecules coupled with their hairpin aptamer probes (H-probes), and the open H-probes hybridized with two different hairpin DNAs containing the G-quadruplex sequence (HG4) to form two different DNA duplexes. These DNA duplexes are then selectively cleaved by the nicking enzyme Nb.BbvCI, which forms the target–H-probe complexes and G-rich DNA segments. The obtained target–H-probe complexes hybridize again with another HG4 to form more DNA duplexes, which initiate continuous enzyme cleavage reaction to form more G-rich DNA segments. Free G-rich DNA segments combine with hemin and K + to form G-quadruplex DNAzymes, which catalyze the CL reaction between hydrogen peroxide (H2 O2 ) and luminol. Finally, G-quadruplex DNAzyme and streptavidin (SA)-functionalised G-quadruplex DNAzyme are quickly separated and detected by the MCE–CL platform. The proposed EMCSA-based MCE–CL method has been applied for simultaneous detection of two significant biomarkers, namely, thrombin (Tb) and carcinoembryonic antigen (CEA), in quantities as low as 2.4 pM and 0.11 ng mL −1 (0.62 pM), respectively. This method for simultaneous detection of two trace disease markers holds great potential in early clinical diagnosis of diseases.